The Participation of HPV-Vaccinated Women in a National Cervical Screening Program: Population-Based Cohort Study. - Eva Herweijer; Adina L Feldman; Alexander Ploner; Lisen Arnheim-Dahlström; Ingrid Uhnoo; Eva Netterlid; Joakim Dillner; Pär Sparén; Karin Sundström (PLoS ONE)
Background Concerns have been raised that HPV-vaccination might affect women's cervical screening behavior. We therefore investigated the association between opportunistic HPV-vaccination and attendance after invitation to cervical screening. Methods A cohort of all women resident in Sweden, born 1977-1987 (N=629,703), and invited to cervical screening, was followed October 2006 - December 2012. Invitations to screening were identified via the National Quality Register for Cervical Cancer Prevention, as was the primary outcome of a registered smear. Vaccination status was obtained from two nationwide health data registers. Hazard ratios (HR) were estimated using Cox regression adjusted for age, education level and income (HRadj). Women were individually followed for up to 6 years, of which the first and second screening rounds were analyzed separately. Results Screening attendance after three years of follow-up was 86% in vaccinated women (N=4,897) and 75% in unvaccinated women (N=625,804). The crude HR of screening attendance in vaccinated vs. unvaccinated women was 1.31 (95% CI 1.27-1.35) in the first screening round. Adjustment for education and income reduced but did not erase this difference (HRadj=1.09, 95% CI 1.05-1.13). In the second screening round, attendance was likewise higher in HPV-vaccinated women (crude HR=1.26, 95% CI 1.21-1.32; HRadj=1.15, 95% CI 1.10-1.20). Conclusions HPV-vaccination is so far associated with equal or higher attendance to cervical screening in Sweden in a cohort of opportunistically vaccinated young women. Most but not all of the difference in attendance was explained by socioeconomic differences between vaccinated and unvaccinated women. HPV vaccine effectiveness studies should consider screening attendance of HPV-vaccinated women when assessing incidence of screen-detected cervical lesions.